2021
DOI: 10.31275/20211903
|View full text |Cite
|
Sign up to set email alerts
|

Two Replication Studies of a Time-Reversed (Psi) Priming Task and the Role of Expectancy in Reaction Times

Abstract: Two experiments involving an international collaboration of experimenters sought to replicate and extend a previously published psi experiment on precognition by Daryl Bem that has been the focus of extensive research. The experiment reverses the usual cause–effect sequence of a standard psychology experiment using priming and reaction times. The preregistered confirmatory hypothesis is that response times to incongruent stimuli will be longer than response times to congruent stimuli even though the prime has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…(2011) more informed prior distribution for effect size, N (0, 0.304 2 ): BF 10 = 1.41, µ = 0.067, 95% CI [−0.111, 0.226]. These results are in line with failed replication studies (e.g., Galak et al, 2012;Ritchie et al, 2012;Schlitz et al, 2021;Wagenmakers et al, 2012) and common sense (Hoogeveen et al, 2020; see also Bem et al, 2011;Francis, 2012;Rouder and Morey, 2011;Schimmack, 2015Schimmack, , 2018Wagenmakers et al, 2011).…”
supporting
confidence: 52%
“…(2011) more informed prior distribution for effect size, N (0, 0.304 2 ): BF 10 = 1.41, µ = 0.067, 95% CI [−0.111, 0.226]. These results are in line with failed replication studies (e.g., Galak et al, 2012;Ritchie et al, 2012;Schlitz et al, 2021;Wagenmakers et al, 2012) and common sense (Hoogeveen et al, 2020; see also Bem et al, 2011;Francis, 2012;Rouder and Morey, 2011;Schimmack, 2015Schimmack, , 2018Wagenmakers et al, 2011).…”
supporting
confidence: 52%
“…The reverse-congruency effect for non-English words echoes a nonsignificant trend within a recent replication attempt of the retroactive priming effect. Specifically, results from English-only participants showed the canonical significant congruency effect (response times on congruent trials faster than incongruent trials), while results from mixed and non-English groups showed a tendency (albeit not significant) for the reverse effect, similar to the one found in our study (Schlitz et al, 2021; Tables 1 and 3). Could culture have played a role in all of this?…”
Section: Discussionsupporting
confidence: 85%
“…(2011) more informed prior distribution for effect size, N (0, 0.304 2 ): BF 10 = 1.41, µ = 0.067, 95% CI [−0.111, 0.226]. These results are in line with failed replication studies (e.g., Galak et al, 2012;Ritchie et al, 2012;Schlitz et al, 2021;Wagenmakers et al, 2012), evidence of QRPs (Alcock, 2011;Francis, 2012;Schimmack, 2012), and common sense (Hoogeveen et al, 2020; see also Bem et al, 2011;Rouder and Morey, 2011;Schimmack, 2015Schimmack, , 2018Wagenmakers et al, 2011).…”
Section: Combining Selection Models and Pet-peesementioning
confidence: 54%